Um sistema multiagente baseado em ontologias para apoio às inspeções de garantia da qualidade de software - Silva, João Pablo Silva da (Universidade do Vale do Rio do Sinos, 2010)
This work presents a support system for inspection of software quality assurance, based on ontologies and agents, which aims at automation of specific activities in a process inspection. The ontology, developed with the Ontology Development 101 method, maps the minimum and necessary concepts to represent the domain knowledge of quality assurance inspections. The agent, development with iterative and incremental method, and specified with the Unified Modeling Language, implements a set of criteria for the handling of individuals in the ontology. The web interface prototype enables the interaction with the agent and ontology, respectively. The system is verified through individual and integrated testing, and is validated through experiments on a real environment of use. The collection of data for comparison occurs in two moments before the use of the system and after using the system. Finally, it is concluded that the system provides a significant gain in coverage of inspections and the maintenance of both the
Keywords: agente; ontologia; garantia da qualidade; agent; ontology; quality assurance; Ciências Exatas e da Terra